Parasitological investigation of children's sand boxes and dog faeces from public areas in old housing districts of Prague - Valkounová, J (Folia parasitologica, 1982)
Eggs and oocysts of 11 species of parasites were recorded in 21 of 50 sand boxes (200 samples) and in 66 (13.2%) of 500 dog faeces samples from parks and grassy areas in Prague. Toxocara canis was found in 12 sand boxes and in 4.2% of faeces samples and T. cati in one sand box and one sample of dog faeces.
Keywords: Toxocara; psi; Feces; cizopasní červi; Play and Playthings; rekreace; Československo; hra a hračky; Animals; feces; Helminths; Dogs; Isospora; zvířata; Recreation; Czechoslovakia